Involvement of rRNA biosynthesis in the regulation of CUC1 gene expression and pre-meristematic cell mound formation during shoot regeneration - Shinohara, Naoki; Ohbayashi, Iwai; Sugiyama, Munetaka (Frontiers in Plant Science, 2014)
At an early stage of shoot regeneration from calli of Arabidopsis, pre-meristematic cell mounds develop in association with localized strong expression of CUP-SHAPED COTYLEDON (CUC) genes. Previous characterization of root initiation-defective 3 (rid3), an Arabidopsis mutant originally isolated as being temperature-sensitive for adventitious root formation, with respect to shoot regeneration implicated RID3 in the negative regulation of CUC1 expression and the restriction of cell division in pre-meristematic cell mounds. Positional cloning has identified RID3 as a WD40 repeat protein gene whose molecular function was not investigated before. Here we performed in silico analysis of RID3 and found that RID3 is orthologous to IPI3, which mediates pre-rRNA processing in Saccharomyces cerevisiae. In the rid3 mutant, rRNA precursors accumulated to a very high level in a temperature-dependent manner. This result indicates that RID3 is required for pre-rRNA processing as is IPI3. We compared rid3 with rid2, a temperature-sensitive mutant that is mutated in a putative RNA methyltransferase gene impaired in pre-rRNA processing, for seedling morphology, shoot regeneration, and CUC1 expression. The rid2 and rid3 seedlings shared various developmental alterations, such as a pointed-leaf phenotype, which is often observed in ribosome-related mutants. In tissue culture for the induction of shoot regeneration, both rid2 and rid3 mutations perturbed cell-mound formation and elevated CUC1 expression. Together, our findings suggest the rRNA biosynthesis may be involved in the regulation of CUC1 gene expression and pre-meristematic cell-mound formation during shoot regeneration.